MOBILE ASSISTED LANGUAGE LEARNING: THE RECENT APPLICATIONS OF EMERGING MOBILE TECHNOLOGIES - Zuhri, Fauris (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The purpose of this paper to describe the rapid developments of smart phone technology and pedagogical application accompanying the process of English learning. Some of the latest research and review has shown that smart phones are contributing significantly to the application of pedagogical process of learning English, which is not limited only to examine the development of smart phone technology itself. Overall, smart phone technology has also been taking part significantly in everyday human life. A discussion of smart phone technology has also been widely known to contribute significantly in the research of Computer Assisted Language Learning (CALL). Many researchers have released their latest report that smart phones contribute positively and effectively at the same time as a support which can improve the quality of English learning process. Challenges and opportunities of smart phone technology has become a matter of everyday discussion.